2014
DOI: 10.1016/j.apsb.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced delivery of hydrophilic peptides in vitro by transdermal microneedle pretreatment

Abstract: The aims of this study were to investigate the utility of solid microneedle arrays (150 µm in length) in enhancing transdermal delivery of peptides and to examine the relationship between peptide permeation rates and D2O flux. Four model peptides were used (Gly–Gln–Pro–Arg [tetrapeptide-3, 456.6 Da], Val–Gly–Val–Ala–Pro–Gly [hexapeptide, 498.6 Da], AC–Glu–Glu–Met–Gln–Arg–Arg–NH2 [acetyl hexapeptide-3, 889 Da] and Cys–Tyr–Ile–Gln–Asn–Cys–Pro–Leu–Gly–NH2 [oxytocin, 1007.2 Da]). The influence of microneedle pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…To assess the validity of the new model, it was used to predict published experimental results [16][17][18][19][20][21] for a variety of drugs permeating across mammalian skin that had been fully porated either using microneedles or by laser ablation; the measured values were also compared to estimates from the intuitive model and the results are presented in Tables 1 and 2. For laser-porated skin, the pore diameter was reported; in the case of microneedle poration, the pore radius (r p ) was calculated from geometric considerations:…”
Section: Resultsmentioning
confidence: 99%
“…To assess the validity of the new model, it was used to predict published experimental results [16][17][18][19][20][21] for a variety of drugs permeating across mammalian skin that had been fully porated either using microneedles or by laser ablation; the measured values were also compared to estimates from the intuitive model and the results are presented in Tables 1 and 2. For laser-porated skin, the pore diameter was reported; in the case of microneedle poration, the pore radius (r p ) was calculated from geometric considerations:…”
Section: Resultsmentioning
confidence: 99%
“…The skin permeation of peptides increases as their molecular weight decreases [21]. In this experiment, we investigated the mass of AMPs separated on portion 5 of 40% polyacrylamide gel and found that it was < 1500 Da (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al . studied the use of solid microneedle arrays (SMNA) (150 μm in length) in transdermal peptide delivery and examined the relationship between peptide permeation rates and D 2 O flux [74]. The influence of MN pre-treatment on skin permeation was evaluated using porcine ear skin with Franze diffusion cell.…”
Section: Microneedle-based Drug Delivery Systemsmentioning
confidence: 99%